Evaluation of 16s Long Read Metabarcoding for Characterizing the Microbiome and Salmonella Contamination of Retail Poultry Meat - Zachary Tobar; Katie Y. Lee; Megan E. Gaa; Bryshal P. Moore; Xunde Li; Maurice E. Pitesky (Journal of Food Protection)
The traditional gold standard for detection of Salmonella in meat products is bacterial culture with enrichment. While this method is highly sensitive, it is slow and provides an incomplete assessment of isolate taxonomy in positive samples. This study presents a novel PCR-based detection assay which amplifies the 16s-ITS-23s region which is an approximately 2,500 base pair region of the larger ribosomal rrn operon. Intra-assay variation was assessed by splitting each biological sample into 3 technical replicates. Limits of detection (LOD) were assessed by utilizing a serial dilution of a pure culture of Salmonella enterica subsp. enterica serovar Heidelberg spiked into either sterile 1 × PBS or 1 × PBS rinsate of a Salmonella culture-negative chicken meat sample. Results indicate the 16s metabarcoding assay evaluated here could not be reliably used for the detection of Salmonella in adulterated retail meat samples as the LOD observed, 4.70 log colony forming units (CFU)/ml, is above the expected concentration of Salmonella in retail poultry meat samples which previous studies have shown range from under 1 to 2 log CFU/ml. However, due to greater taxonomic resolution afforded by using 16s long reads, the assay allowed alpha diversity assessment of the microbiome of raw poultry meat with the ability to assign taxonomy to the species and strain level for some amplicon sequence variants (ASV). This indicates this process may have value characterizing biodiversity and pathogen contamination of poultry samples in earlier steps of the poultry meat production process where bacterial contamination concentrations are likely to be higher.